2018
DOI: 10.1002/tafs.10102
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of PIT Tagging on a Critically Endangered Small‐Bodied Fish: A Trial on the Surrogate Mountain Galaxias

Abstract: Recent advances in PIT technology have led to smaller tags, meaning that this technology can be used to mark and monitor smaller‐bodied species, many of which are threatened. We examined the effects of 9‐mm PIT tags on the survival and growth of the Mountain Galaxias Galaxias olidus, using this fish as a surrogate for several threatened, small‐bodied galaxiids. We measured survival, growth, and tag retention in 34 tagged and 34 untagged fish held in aquaria for 90 d posttagging. Fish were randomly assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A comparison of implantation methods found significantly reduced wound healing for fish tagged by incision compared to syringe [38]. Wound healing is not measured in all tagging studies [5,13,14,30,32,36,[39][40][41][42] (Additional file 2) and may not always be indicative of ill effects of tagging. However, wound healing should be monitored in the interest of fish welfare and ensured that the wound has no significant impact on survival, tag retention, growth, condition and general health.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of implantation methods found significantly reduced wound healing for fish tagged by incision compared to syringe [38]. Wound healing is not measured in all tagging studies [5,13,14,30,32,36,[39][40][41][42] (Additional file 2) and may not always be indicative of ill effects of tagging. However, wound healing should be monitored in the interest of fish welfare and ensured that the wound has no significant impact on survival, tag retention, growth, condition and general health.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a paucity of information regarding the movements of Australian small-bodied freshwater fishes, studies on ephemeral waterholes and genetics (Unmack, Allen & Johnson, 2013) suggest that some of these species are capable of dispersing great distances. The study of dispersal in small-bodied fishes has often been hampered by their size and the consequent limitations in employing individually tagged fish (Allan et al, 2018).…”
Section: Dispersalmentioning
confidence: 99%
“…There is a paucity of movement data for most smaller species (,150-mm total length; e.g. olive perchlet, southern pygmy perch and Murray hardyhead), not just due to size-related limitations of tagging methods (but see Allan et al 2018), but also because they generally receive less attention than largerbodied species (Saddlier et al 2013;Lintermans et al 2020). However, when studies have occurred, large numbers of individuals of many small species have been found to move (Stuart and Berghuis 2002;.…”
Section: Attribute Descriptionmentioning
confidence: 99%
“…and are among the most threatened, yet their perceived insignificance and the difficulty in applying many research approaches (e.g. electronic tagging; but see Allan et al 2018) mean that they have received limited research attention. This must be redressed.…”
Section: Knowledge Assessment and Priority Gapsmentioning
confidence: 99%
See 1 more Smart Citation